Analisis Prediksi Korosi Tulangan pada Beton Busa Bertulang dengan Metode Half Cell Potential Mapping - Fajri Fajri (Jurnal Teknik Sipil Unaya, 2021)
Half-cell potential mapping is a simple non-destructive test method for the corrosion of reinforcing steel. This study aim to analyze the prediction of reinforcing corrosion in reinforced foam concrete using the Haf-Cell Potential Mapping method. The test includes mapping of reinforcing steel and measuring corrosion potential. The speciment is beam of 15cm x 20cm x 80cm size. The main reinforcement is  4Ø10mm and stirrup Ø6-10cm, and concrete cover thickness of 20mm. Cement water rasio is  0,4; specifi gravity 1,6 and compressive strength of 25MPa. The specimens were immersed in a 3,5% sodium chloride solution and in well water as a control. Corrosion potential measurements were carried out every 2 weeks for 16 weeks. The results showed that the corrosion potential value increased due to the duration of immersion. The corrosion potential value of the speciment immersed in NaCl solution is.-300mV, the risk of corrosion is 90%. The corrosion potential value of the speciment immersed in well water is -200mV, the risk of corrosion is at 50%. Foam concrete soaked in seawater has a greater risk of corrosion than in well water. But the risk of foam concrete submerged in seawater is still smaller than conventional concrete submerged in seawater.